Optimalisasi Kompetensi Guru melalui Pelatihan Media Pembelajaran Berbasis Augmented Reality (AR) di SMP Negeri 3 Sitolu’ori, Nias Utara - Toroziduhu Waruwu; Novelina Andriani Zega; Hardikupatu Gulo; Agnes Renostini Harefa; Dasari Waruwu; Nofamataro Zebua; Ester Novi Kurnia Zebua (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2026)
Digital transformation in education requires teachers to be capable of integrating technology into the learning process. However, in reality, the utilization of digital media in schools remains suboptimal, particularly in the use of Augmented Reality (AR)-based learning media. This study aims to analyze the optimization of teachers’ competencies through AR-based learning media training at SMP Negeri 3 Sitolu’ori. The study employed a quantitative descriptive approach with a hands-on practice-based training design. The research subjects consisted of 19 teachers from various subject areas selected using purposive sampling techniques. Data were collected through observations, questionnaires, interviews, and documentation, and were analyzed using descriptive statistics and interactive analysis. The results showed that all research instruments were valid and highly reliable, with Cronbach’s Alpha values of 0.973 and 0.981. Most teachers demonstrated positive perceptions toward the use of AR media, with 87% categorized as good and very good. The training was also considered effective in improving teachers’ readiness, understanding, and confidence in developing technology-based learning. The findings indicate that AR media has significant potential to support interactive and innovative learning, although its implementation still faces challenges related to limited devices and the technical abilities of some teachers.